The effectiveness of total quality management: a response to the critics. - Douglas H. Smith; Ralph G. Lewis (Adult Education Research Conference, 1997)
A recent paper strongly berates total quality management, claiming it is a tool of management used to adversely manipulate workers in pursuit of corporate gain. This paper questions this supposition, arguing it is the abuse of TQM by management that is at fault. Effective TQM is based on four principles, customer satisfaction, continuous improvement, speaking with facts, and respect for people. It is the lack of the genuine respect for people that is the demise of most TQM initiatives.